Induced defense related enzyme activities of tomato plant by indigenous endophytic bacteria and challenged by Ralstonia syzigii subsp. indonesiensis - YULMIRA YANTI; WARNITA WARNITA; REFLIN REFLIN (Indonesian Society for microbiology, 2019)
Our previous research had screened 9 best indigenous endophytic isolates for their ability to control Ralstonia syzigii subsp. indonesiensis, the causal agents of bacterial wilt disease in tomato (Lycopersicon esculentum) in green house condition. Those 9 strains were Bacillus cereus EPL1.1.3, B. cereus TLE2.3, B. toyonensis EPL1.1.4, Serratia nematodiphila TLE1.1, B. anthracis SNE2.2, B. cereus E1.AB1.2, B. cereus E1AB2.1, Enterobacter cloacae subsp. dissolvens TLE2.2 and S. marcescens KLE3.3. The purposed of this study is to test the ability of the endophytic bacteria strains in increasing defense related enzyme activities of tomato. Bacterial strains were tested for its ability to induce the defense-related enzymes which were phenylalanine ammonia lyase (PAL), peroxidase (PO) and polyphenol oxidase (PPO) in roots and leaves of tomato plants. R. syzigii subsp. indonesiensis inoculated to host plants 7 days after the endophyte bacteria strains inoculation. Enzyme activities were recorded at 0, 1, 3, 5, 7, 9, 12 and 15 days after pathogen inoculation (dpi). Â It was observed that PAL, PO and PPO activities were significantly increased in all of the endophytic bacteria inoculated treatments compared to control plant. Activities of PAL in the leaves was fast similar to the roots; but PO activities was higher in the roots compared to that in the leaves, whereas PPO activities was higher in the leaves than in the roots. PAL and PO reached the maximum level at different time in the leaves (3 dpi and 15 dpi), in the roots (5 dpi and 12 dpi), whereas PPO in the leaves at 12 dpi and in the roots at 9 dpi.